2009
DOI: 10.1007/s12892-009-0075-y
|View full text |Cite
|
Sign up to set email alerts
|

Production of phenolic compounds in hairy root culture of tartary buckwheat (Fagopyrum tataricum Gaertn)

Abstract: Fagopyrum tataricum Gaertn (tartary buckwheat) is an excellent medicinal and nutrient-rich crop. It has a high content of rutin and other phenolic compounds. An experiment was conducted to investigate in vitro production of phenolic compounds from hairy root culture of tartary buckwheat. Hairy root growth was promoted by increasing culture time in MS medium. The highest hairy root growth reached up to 11.2 g/l dry weight at 18 d after placement. Transformation was confirmed by PCR using rol genes, rol A (304 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 29 publications
1
40
0
Order By: Relevance
“…The present study exhibited that hairy roots contained higher amount of individual phenolic compounds compared to non-transgenic plants. Similarly, phenolic acid derivatives such as chlorogenic acid and quercetin were presented higher amount in hairy roots when compared with wild type roots of F. tataricum (Kim et al, 2009).…”
Section: Comparison Of Individual Phenolic Compounds In Transgenic Hamentioning
confidence: 93%
See 1 more Smart Citation
“…The present study exhibited that hairy roots contained higher amount of individual phenolic compounds compared to non-transgenic plants. Similarly, phenolic acid derivatives such as chlorogenic acid and quercetin were presented higher amount in hairy roots when compared with wild type roots of F. tataricum (Kim et al, 2009).…”
Section: Comparison Of Individual Phenolic Compounds In Transgenic Hamentioning
confidence: 93%
“…Transformed roots yielded higher levels of catechin and epicatechin than untransformed roots of H. perforatum (Tusevski and Simic, 2013). Kim et al (2009) reported that the rutin and epicatechin contents in hairy roots were several-fold higher than those in non-transgenic roots of Fagopyrum tataricum . Kaempferol, myricetin, naringin, quercetin and rutin have antimicrobial activity against human pathogenic microorganisms with some mechanisms of action such as inhibition of nucleic acid synthesis, cytoplasmic membrane function and energy metabolisms (Cushnie and Lamb, 2005).…”
Section: Comparison Of Individual Phenolic Compounds In Transgenic Hamentioning
confidence: 99%
“…Accumulation of phenolic compound in wild and hairy root of F.tataricum was compared [38]. They reported that phenolic content in hairy roots were several fold higher than wild type roots of same species.…”
Section: Resultsmentioning
confidence: 99%
“…Phenolic compound production by hairy root culture of F . tataricum has also been reported (Kim et al. , 2009).…”
Section: Introductionmentioning
confidence: 92%